2013
DOI: 10.1097/qai.0b013e31827ce4ee
|View full text |Cite
|
Sign up to set email alerts
|

Renal Impairment in Patients Receiving a Tenofovir-cART Regimen

Abstract: The high prevalence of elevated Ctrough-TDF and its correlation with an increased risk of renal impairment support the usefulness of therapeutic drug monitoring for TDF, particularly in women and older patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
29
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 20 publications
7
29
2
Order By: Relevance
“…There is evidence of an association between tenofovir plasma concentrations and renal toxicity (4,6,7,14). A study by Rodríguez-Nóvoa et al has shown that patients with a tenofovir plasma concentration of more than 160 ng/ml at middose (10 to 14 h after the last dose) were at a 4.8 times higher risk of experiencing KTD than patients with a tenofovir plasma concentration below this cutoff value (6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is evidence of an association between tenofovir plasma concentrations and renal toxicity (4,6,7,14). A study by Rodríguez-Nóvoa et al has shown that patients with a tenofovir plasma concentration of more than 160 ng/ml at middose (10 to 14 h after the last dose) were at a 4.8 times higher risk of experiencing KTD than patients with a tenofovir plasma concentration below this cutoff value (6).…”
Section: Discussionmentioning
confidence: 99%
“…The cutoff values of the middose (12-h) tenofovir concentration (C 12 ) and the trough (minimum) concentration (C min ) (Ͼ160 ng/ml and Ͼ90 ng/ml, respectively) were proposed to discriminate a risk of kidney tubular dysfunction (KTD) (6,7). These results suggest that genetic variation in tenofovir transporter genes may lead to overexposure to tenofovir, resulting in kidney tubular cell damage.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…While in clinical reports, the impact of TDF on renal function is mostly described in terms of decrease of estimated glomerular filtration rate (GFR), TDF appears unlikely to directly harm any glomerular structure and its effect on GFR estimation depends upon the decreased creatinine secretion that is secondary to tubular dysfunction (3). In four independent clinical studies, TDF pharmacokinetic (PK) exposure was found to be associated with alterations in a series of renal function markers, both glomerular and tubular (4)(5)(6)(7). According to drug-drug interaction studies of healthy volunteers, the PK exposure of tenofovir seems to be rather sensitive to the choice of companion drugs, which suggests that, depending on the specific HAART regimen, its impact on tubular function may also vary.…”
mentioning
confidence: 99%
“…30,31 Our data showed that the use of tenofovir combined with a protease inhibitor increased the risk of kidney disease (abnormal eGFR and abnormal UPC or UAC ratios), as previously described in large cohorts. 15,22,32 Higher tenofovir plasma concentration was associated with alterations in renal markers (both glomerular and tubular), 33,34 and the highest plasma exposure was associated with the concomitant use of protease inhibitors. 35 However, whether co-administered or not with protease inhibitors, tenofovir was not associated with proteinuria > 300 mg/g in our cohort.…”
Section: Discussionmentioning
confidence: 99%